Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Keinginan Keluar Pada Bali Nature Land Tour, Tabanan - Listiniasih, Ni Putu Dewi; Mujiati, Ni Wayan (E-Jurnal Manajemen, 2015)
Intention to leave is a phenomenon that is often encountered in a company. The purpose of this study was to determine the effect of job satisfaction and organizational commitment to the wishes out either directly or indirectly, to determine the variables that affect intention to leave . Bali Nature Land Tour, Tabanan be the location of respondents as many as 43 employees. Data analysis techniques are used to test the hypothesis is path analysis aimed to determine the effect, directly or indirectly, one dependent variable and one or more independent variables. The analysis showed that the variables of job satisfaction has positive influence on organizational commitment, job satisfaction negatively affect the willingness and commitment of the organization out positive effect on desire out. Recommendations for future research, is to expand the area or location given the limitations of the study researchers looked only at one place Bali Nature Land Tour, Tabanan and future research should develop a research model by adding other variables .
Keywords: job satisfaction, organizational commitment, intention to leave